Heparanase level and procoagulant activity are reduced in severe sepsis. (1st December 2017) - Matan, Moshe; King, Daniel; Peled, Eli; Ackerman, Shanny; Bar‐Lavi, Yaron; Brenner, Benjamin; Nadir, Yona
Abstract: Background: During severe sepsis, levels and activity of all coagulation proteins are reduced. Heparanase is implicated in angiogenesis and tumor progression. We previously demonstrated that heparanase also affected the hemostatic system. It forms a complex and increases the activity of the blood coagulation initiator tissue factor. Aim: To evaluate heparanase levels and procoagulant activity as predictors of sepsis severity. Materials and Methods: Twenty‐one patients with non‐trauma, non‐surgical sepsis admitted to the intensive care unit and 35 controls were recruited. Plasma samples were drawn from the study participants on days 1 and 7 following admission. Results: Heparanase levels and procoagulant activity on day 1 were significantly reduced in patients compared to controls ( P < .0001, P < .0001, respectively). Day 1 heparanase procoagulant activity ≥350 ng/mL yielded a negative predictive value for severe sepsis of 89%. Additionally, heparanase procoagulant activity on day 7 correlated with the change in the APACHE score between days 1 and 7 ( r = .66, P = .007). Conclusions: Heparanase procoagulant activity decreases during sepsis and returns to normal levels as soon as the patient recovers. Hence, it can be potentially used to predict the risk of severe sepsis. These findings need to be further explored in large‐scale studies.